Primary Lymphangiosarcoma of the Urinary Bladder in a Dog. (August 2020) - Michishita, M.; Ishizaki, Y.; Konnai, M.; Machida, Y.; Nakahira, R.; Hatakeyama, H.; Yoshimura, H.; Yamamoto, M.; Soeta, S.; Ochiai, K.; Misawa, K.; Yugeta, N.; et al.
Summary: Abdominal ultrasonographical and computed tomography examinations of a 12-year-old neutered female toy poodle revealed a protruding mass, approximately 2 cm in diameter, at the apex of the bladder. The mass was firm and haemorrhagic with a homogeneously brownish–yellow cut surface. Microscopically, it was unencapsulated and located in the muscle layer with invasion of the extra-muscular layer. It was composed of spindloid to oval neoplastic cells that formed irregular clefts and diffuse sheets that dissected bundles of collagen. Immunohistochemically, the neoplastic cells were positive for vimentin and lymphatic vessel endothelial hyaluronan receptor 1 antigens, but negative for cytokeratin AE1/AE3, factor VIII-related antigen, CD31, CD34, Prox-1, S100, desmin, α-smooth muscle actin and MyoD1. Negative immunolabelling for laminin antigen supported the absence of evidence of a basal lamina on ultrastructural examination. Based on these findings, this tumour was identified as a lymphangiosarcoma. To the best of our knowledge, this case is the first report of lymphangiosarcoma arising from the bladder in a dog.